A Bibliometric Review of Institutional Theory on Higher Education Institutions - Hsu, Pang Lien; Maccari, Emerson Antonio; Mazieri, Marcos Rogério; Storopoli, José Eduardo (Future Studies Research Journal: Trends and Strategies, 2018)
In this study, we explore how institutional theory and its many subareas contributes, are utilized and applied to the area of higher education management’s research by their scholars. For this purpose, we performed a bibliometric analysis on 659 papers extracted from Web of Science database. As results we indicate five main clusters as foundation to the field: institutional theory; economic impact of entrepreneurship and universities; competitiveness of universities as businesses; service quality and; measurement and development of models for higher education. And 7 main clusters as subfields of research: Institutional Multiplicity; Institutional pressures on Higher Education; Higher Education Efficiency; Leadership in Higher Education; Entrepreneurial Higher Education; Academy & Professional relations and; Quality and Satisfaction in Higher Education.